Method development of quercitrin enrichment from asthma-plant (Euphorbia hirta L.) using aromatic macroporous resin - Sumail Sidik Ode Ishak; Amrianto; Diah Astari Salam; Rika Hartati (Institut Teknologi Bandung, 2022)
Asthma-plant contains high amount of quercitrin which make it a potential new source for flavonoids. This study aims to develop a method of quercitrin enrichment by utilizing macroporous resin, which is known to be safer, more eco-friendly, economics, and efficient. Evaluations were conducted over the performance and separation characteristics of the macroporous resin in quercitrin enrichment as well as the adsorption and desorption of quercitrin by the macroporous resin. The results showed that the adsorption process of the macroporous resin in relation to the amount of quercitrin in the extract were in accordance with the second order model, which means that the process of adsorption is affected by other compounds. Furthermore, the examination of the isotherm adsorption fit the Freundlich’s model (R2 = 0.9850) rather than the Langmuir’s one (R2 = 0.4334). In the optimal condition, the enrichment of quercitrin by using macroporous resin increased the abundance of quercitrin by nearly five times, from 3.60% of quercitrin content in the extract to 17.02% in the quercitrin-rich fraction, with recovery yield of 50.39%.